The impact of electronic procurement adoption on green procurement towards sustainable supply chain performance-evidence from Malaysian ISO organizations - Pratik Kumar Singh; Chan Shiau Wei (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Emerging technologies such as electronic procurement have rapidly become common practice in recent years. With the advent of internet technologies and open innovations, the traditional procurement system is transformed into an electronic procurement system. Technology adoption is influenced by multiple factors, including the adopter, technology, and ecosystem in which they function. Considering this, E-procurement is still being adopted slowly. This research aims to investigate the extension of the adoption of E-procurement and identify the relationships between the E-procurement technologies and green procurement practices across different sectors of ISO 14001- certified Malaysian enterprises. This research is supported by the Technology Acceptance Model, one of the significant theories of technology adoption. Using SPSS and SmartPLS, the survey data is analyzed quantitatively. The structural model explains 86% of the variance in green procurement and shows the positive significant relationship between green procurement and the E-procurement technology of the ISO 14001 firms. Consequently, adopting E-procurement technology would benefit company sustainability. A benchmark for ISO companies will be established, highlighting the importance of E-procurement technology in improving green procurement and supply chain efficiency. The study recommends that demand for environmentally friendly products and services be fueled by technology-based purchases, resulting in a greener supply chain.
Keywords: 650; electronic procurement; E-procurement; green procurement; open innovation; sustainableprocurement; sustainability; supply chain performance; TAM; ISO 14001